ISLAMIC BOARDING SCHOOL: THE BEST INVESTMENT FOR THE FUTURE OF EDUCATION - Haris, Abdul; Manshur, Umar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This article discusses the importance of Islamic boarding schools as the best investment for the future of education. Islamic boarding schools, as traditional Islamic educational institutions in Indonesia, provide religious education and equip students with life skills and academic knowledge. The research methods used are literature studies and interviews with the caretakers of the Islamic boarding schools. The survey results show that Islamic boarding schools significantly contribute to producing a generation with noble character, broad knowledge, and readiness to face future challenges. Islamic boarding schools also play an essential role in strengthening Islamic identity and local culture in Indonesia. In addition, Islamic boarding schools are also a place for students to develop independence, leadership, and togetherness. Thus, Islamic boarding schools are not only places to study but also places that change the mindset and attitude of students to become strong and competitive individuals. In addition, Islamic boarding schools also provide space for students to develop their potential and talents so that they can make a positive contribution to society and the nation.